Determinants of corporate cash holdings for the UK companies - XIE, Yige (2017)
This dissertation investigates the determinants of public quoted and public A.I.M UK companies’ cash holdings during the sample period 2008 to 2016. The regression results have suggested that the most influential factors for corporate cash holdings are respectively leverage, liquidity, and the investment & growth opportunities. We found that all of these three determinants have substantial positive impacts on the reserve of corporate cash & equivalents. Moreover, the data analyses have also suggested that larger corporations tend to hold less cash and liquid assets than the small & medium sized companies. In addition, qualitative factors are likely to have influences on the corporate cash holdings as well, yet measurement and collection for such variables can be rather difficult and time consuming.